SISTEM REKOMENDASI PEMILIHAN ROUTER MIKROTIK UNTUK SKALA SOHO DENGAN METODE WASPAS - Susanto, Handy; Sidiq Purnomo, Agus (Journal of Innovation And Future Technology (IFTECH), 2024)
In an increasingly digital era, the need for reliable and efficient internet connectivity has become a top priority for small businesses and home offices (SOHO). In managing the internet network, equipment is needed that can manage the network, namely a router. This research aims to determine the best router that can meet network needs in a SOHO environment using the Weighted Aggregated Sum Product Assessment (WASPAS) method. This study evaluates several MikroTik router models based on important criteria such as performance, reliability, WiFi technology and cost. The results of the WASPAS analysis show that the MikroTik C52iG-5HaxD2HaxD-TC (hAP ax2) router is the best with the highest aggregate value of 0.95. With this value, the hAP ax2 router is proven to be superior in providing optimal network solutions for SOHO businesses, ensuring the stability and connection speed needed to support daily business activities